A Production and operations management study on Master Breader, Inc. - Cardonas, Dorothy (College of Engineering, 1997)
Master Breader, Inc. Is a medium-scale bread manufacturing firm that is presently facing capacity problems. It is becoming more and more difficult for them to meet the increasing demands of their main customer. Since bread is a highly perishable item, it is not advisable for them to keep large quantities of safety stock, so it is imperative that they be capable of producing the required amounts at short notice. The group was able to pinpoint three major P / OM problems for the company. These are: 1) A lack of forecasting technique for demand; 2) Frequent hiring and lay-off of workers; and 3) Failure of production capacity to meet demand requirements. For each major problem, alternatives were proposed and analyzed using cost-benefit analysis. For the lack of forecasting technique, the group recommended that the company employ FITS (Forecasting Including Season and Trend) because demand is steadily increasing and at the same time affected by seasonal factors. Daily demand was determined by obtaining relative percentages of the weekly forecasts. These percentages were computed bearing in mind the alternating increases and decreases in daily demand. For the second problem which is concerned with workforce level, it is recommended that the mixed strategy be used for each major manual process. This strategy generated the least costs against three other alternatives (chase, level, and status quo). The third problem, which concerns capacity issues, was addressed by increasing the number of machines and workers per major manual process in order to meet the average foretasted daily demand. Aside from the fact that the company can now meet a higher level of demand, a considerable amount of profit is earned by simply utilizing idle machines and purchasing new equipment. An area for further study is to determine the feasibility of expansion, to further increase capacity and hopefully capture a larger market share.